The contribution of services trade policies to connectivity in the context of aid for trade - Martin Roy (World Trade Organization (WTO), 2017)
This paper examines how services trade and policies contribute to connectivity. It highlights the economic relevance of services and identifies some key channels through which trade in services contributes to physical and digital connectivity. The paper examines the impact of services trade policies on connectivity in view of recent research showing their impact on sectoral performance, economic welfare and development. Finally, it discusses the positive contribution that aid for trade can make in support of services policies. The paper finds that services sectors play a multifaceted and significant role in connecting countries to the international trading system, and matter greatly to economic development and the achievement of the Sustainable Development Goals (SDGs). Services significantly affect connectivity by: (i) providing the basic infrastructure to support trade in goods; (ii) facilitating supply chains and entering trade as value added embodied in goods; (iii) providing the backbone that enables e-commerce and the on-line supply of services; (iv) and enhancing export diversification through their cross-border electronic supply. The paper underscores that services trade policies have a fundamental impact on connectivity. Restrictions to investment and cross-border trade in services remain high and widespread. But an enabling policy environment - promoting competition, openness to trade and investment, and adequate regulatory frameworks - can enhance connectivity, lower trade costs, and foster growth and economic performance. For example, improving the policy environment for services sectors can help attract the FDI required to meet the SDGs and develop the ICT infrastructure needed to bridge the digital divide. Aid for Trade can play a supportive role in this regard.
Keywords: F13; F15; F53; L8; L96; 330; WTO; GATS; trade in services; aid for trade; digital trade